From conventional to inverse magnetocaloric effect in GdMn1-xCrxO3. Issue 1 (31st December 2022) - Hamad, Mahmoud A.; Alamri, Hatem R.
Abstract : In this work, a phenomenological model (PM) is used to simulate the magnetocaloric effect (MCE) of GdMn1- x Cr x O3 (0 ≤ x ≤0.4) (GMCO) samples through the modelling of experimental isofield thermo-magnetization curves. The results showed that the MCE of GMCO samples depends strongly on Cr content, achieving a conventional MCE for low Cr content (level of doping x  ≤ 0.3). However, the MCE of a higher Cr content sample has an inverse MCE. The behaviour of MCE in GMCO samples indicated that GMCO compounds are interesting magnetocaloric materials and can fruitfully be functioned as cryogenic magnetic refrigerants below 40 K especially in radiation detectors for outer space research.